VR environment of digital design laboratory: a usability study - Alnuaimi, Mariam Ali; Awad, Mamoun (Frontiers in Virtual Reality, 2025)
IntroductionVirtual reality (VR) offers an immersive learning environment with the potential to revolutionize how students engage with complex topics and interact during classes. Great care must be taken when designing and developing VR applications. In this paper, we present a usability study of our proposed educational VR application designed for the digital design and computer organization lab. The VR-lab is meant to support the traditional lab that is taught in college first year.MethodsTo assess the VR application, we conducted a usability study with a wide range of students from different colleges, evaluating their performance on tasks within the VR environment and collecting their feedback on the application’s design, functionality, and ease of usage. By analyzing quantitative data (task completion rates and time spent) and qualitative feedback (surveys and observations), in this study, we identified potential usability issues and recommended improvements to enhance the learning experience within the VR application.ResultThe usability study showed that the majority of students found that the VR application immersive, engaging, and viewed their experience as helpful to better understand complex concepts. With confidence level of 95%, the VR application had significant improvement on students’ learnability, memorability, and the average task completion time.DiscussionAdditionally, in the study, we found that careful design and technology must be used selectively due to population variation in terms of technology knowledge level, health factor, and readiness.